Regional Genetic Structure in the Aquatic Macrophyte Ruppia cirrhosa Suggests Dispersal by Waterbirds - Martínez-Garrido, Jose; Bermejo-Lacida, Ricardo; Serrao, Ester A; Sánchez-Lizaso, J; González-Wangüemert, Mercedes (Springer, 2017)
The evolutionary history of the genus Ruppia has been shaped by hybridization, polyploidisation and vicariance that have resulted in a problematic taxonomy. Recent studies provided insight into species circumscription, organelle takeover by hybridization, and revealed the importance of verifying species identification to avoid distorting effects of mixing different species, when estimating population connectivity. In the present study, we use microsatellite markers to determine population diversity and connectivity patterns in Ruppia cirrhosa including two spatial scales: (1) from the Atlantic Iberian coastline in Portugal to the Siculo–Tunisian Strait in Sicily and (2) within the Iberian Peninsula comprising the Atlantic–Mediterranean transition. The higher diversity in the Mediterranean Sea suggests that populations have had longer persistence there, suggesting a possible origin and/or refugial area for the species. The high genotypic diversities highlight the importance of sexual reproduction for survival and maintenance of populations. Results revealed a regional population structure matching a continent–island model, with strong genetic isolation and low gene flow between populations. This population structure could be maintained by waterbirds, acting as occasional dispersal vectors. This information elucidates ecological strategies of brackish plant species in coastal lagoons, suggesting mechanisms used by this species to colonize new isolated habitats and dominate brackish aquatic macrophyte systems, yet maintaining strong genetic structure suggestive of very low dispersal.
Keywords: Rupiáceas; Ruppia; Connectivity patterns; Genotypic diversity; Waterfowl; Coastal lagoon